Some procedures of perioperative care in aspect of ostomy - Cierzniakowska, Katarzyna; T. Szewczyk, Maria; Cwajda, Justyna; Stodolska, Alina; Jawień, Arkadiusz; Banaszkiewicz, Zbigniew (Przewodnik Lekarza/Guide for GPs, 2005)
Modern nursing is associated with following terms: nursing process, nursing care models, holistic care, quality of care, standards, procedures, algorythms of nursing care. Nurses are well prepared for care of patients with colon illnesses thanks to specialist knowledge and experience, especially for perioperative preparation and care after procedure. Abdominal surgery, especially colon, is associated with nursing problems due to ostomy. This article discusses selection of nursing care procedures in aspect of ostomy during perioperative care.